Integrasi Pengetahuan Digital dan Nilai Agama dalam Akselerasi Internasionalisasi UMKM Gresik - Rohman, Abid; Nurika, Rizki Rahmadini; Hidayatullah, Nur Luthfi; Rosyidi, Zudan; Alfin, Jauharoti (The Sociology of Islam, 2025)
Knowledge plays a strategic role as a catalyst for socio-economic transformation, including in advancing the internationalization of Micro, Small, and Medium Enterprises (MSMEs). In Gresik Regency, the transition toward global markets is shaped not only by digital literacy and managerial capacity but also by Islamic religious values that influence entrepreneurs’ awareness, motivation, and business orientation. This study aims to explore the subjective experiences of MSME actors in Srowo in integrating digital literacy and export knowledge with Islamic values in their internationalization efforts. Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations, focusing on lived experiences and reflections on the relationship between business practices, digital technology use, and religious beliefs. Phenomenological reduction was applied to identify the essence of collective experiences. Findings reveal that knowledge and religion are perceived as an integrated unity of professional endeavor and spiritual commitment. Digital literacy is understood not merely as a technical tool but as a moral responsibility to conduct halal, honest, and ethical business, reinforcing entrepreneurial resilience and identity in global markets.